SAT0606 Impact of Musculoskeletal Ultrasound in Treatment Decision in Routine Daily Care of Rheumatoid Arthritis (Impulsar Study). (9th June 2015) - Toniolo, E.; Díaz-Torné, C.; Moragues, C.; Geli, C.; Millán, M.; Castellví, I.; Moya, P.; Laíz, A.; Llobet, J.M.
Abstract : Background: Remission or low disease activity is the therapeutic target in the ACR-EULAR recommendation for the management of rheumatoid arthritis (RA). In multiple studies, musculoskeletal ultrasound (US) has shown to be more reliable and sensitive than physical examination in both the diagnosis and the assessment of RA activity. However, the real impact of this technique on routine daily care of RA and treatment decisions has not been studied. Objectives: To assess the proportion of therapeutic decisions that are modified by the results of the US examination in patients with RA. To determine which group of patients would get more benefit from a musculoskeletal US to optimize treatment. Methods: Seventy eight consecutive patients diagnosed with RA by ACR 1987 criteria and visited between July and November 2014, were included. All patients were initially visited by their usual rheumatologist and a therapeutic decision was made according to physical examination and clinical and laboratory findings. Subsequently, a musculoskeletal US was performed by an expert sonographer of our center and the usual rheumatologist was asked to reassess his therapeutic decision in light of the US findings. We classified the change in the therapeutic attitude as: negative (maintenance of therapeutic attitude) and positive (increase or reduction in treatment, compared to the initial decision). Demographic, clinical and laboratory data were collected from the clinical history and activity scores were calculated. Results: Clinical, demographic, laboratory, treatment and activity score data are shown in table below. In 29 patients [37.2% (95% CI 26.5 to 48.9)] the findings in the US examination conditioned a change in the therapeutic decision of the usual rheumatologist. In 18 patients (62.07%) the change was towards an intensification of treatment, while in 11 patients (37.93%) a decrease was possible. Change of treatment was more frequent in patients with intermediate disease activity (mild and moderate activity) than in those with extreme activities (remission and high activity), 41.4% vs 25%, although this difference was not statistically significant. A higher frequency of change was found in men (53.8% vs 33.8%) and erosive RA forms (43.6% vs 21.7%), but the results did not reach statistical significance. Conclusions: Musculoskeletal ultrasound, when added to routine rheumatologic investigation, is an important tool for treatment decisions in the routine daily care of rheumatoid arthritis. Patients with intermediate activities of the disease might get more benefit from the use of an US examination. Disclosure of Interest: None declared